PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN STOCKFIT PADA PT ADIS DIMENSION FOOTWEAR KABUPATEN TANGERANG - Bagas Arianto; Temmy Setiawan; Khaerul Fahmi (Desanta Publisher, 2026)
The Influence of Workload and Work Environment on Employee Performance in the Stockfit Department at PT Adis Dimension Footwear, Tangerang Regency. This study examines the partial and simultaneous effects of workload and work environment on employee performance. Using a quantitative descriptive method with 61 respondents, the results show that workload and work environment significantly affect employee performance.